2019
DOI: 10.1088/1755-1315/295/5/052030
|View full text |Cite
|
Sign up to set email alerts
|

Phosphogypsum pyrolysis with mineralization agent under weak reducing atmosphere

Abstract: Batch experiments of phosphogypsum (PG) pyrolysis were carried out under weak reducing atmosphere, adding coke as reductant and CaF2 as mineralization agent. As 3 wt% CaF2 was added to the mixture, the optimal parameters of PG decomposition were mole ratio (C: CaSO4) 0.7, reaction temperature 950 °C, pyrolysis time 60 min, and 1.9-2.2% oxygen content of inlet gas. Under this condition, the decomposition ratio of CaSO4 was up to 90.6%, the SO2 conversion was 70.4%, and the average volume concentration of SO2 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…In summary, it can be concluded that the amount of reducing agent and smelting temperature are the key factors affecting the desulfurization effect and slag phase structure in the new process of acid-making and slag wool production based on phosphogypsum. It was appropriate to add the reductant with a C/S molar ratio of 0.5–0.8, which was consistent with the previous research results . The desulfurization effect of phosphogypsum can be greatly improved in the molten state due to the enhanced mass and energy transfer.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In summary, it can be concluded that the amount of reducing agent and smelting temperature are the key factors affecting the desulfurization effect and slag phase structure in the new process of acid-making and slag wool production based on phosphogypsum. It was appropriate to add the reductant with a C/S molar ratio of 0.5–0.8, which was consistent with the previous research results . The desulfurization effect of phosphogypsum can be greatly improved in the molten state due to the enhanced mass and energy transfer.…”
Section: Resultssupporting
confidence: 86%
“…It was appropriate to add the reductant with a C/S molar ratio of 0.5–0.8, which was consistent with the previous research results. 53 The desulfurization effect of phosphogypsum can be greatly improved in the molten state due to the enhanced mass and energy transfer. The XRD patterns of the slags obtained above 1300 °C were all amorphous structures, which were the same as those at 1300 °C in Figure 6 d and were no longer listed.…”
Section: Resultsmentioning
confidence: 99%